Study of Point Scanning Detection Mechanisms for Vibration Signals with Wavefront Sensors - Quan Luo; Hongsheng Luo; Yiyou Fan; Guihan Wu; Haoming Chen; Yun Pan; Wei Jiang; Jinshan Su (Photonics)
Seismic wave laser remote sensing is extensively employed in seismic monitoring and resource exploitation. This work establishes a vibration signal point scanning detection system utilizing wavefront sensors, leveraging their high resolution, array detection capabilities, and the independent detection of each microlens based on research into seismic wave laser remote sensing detection. The experiments validate that each microlens of the wavefront sensor possesses autonomous detecting capabilities, enabling the sensor to scan and identify points of vibrational signals. This work also significantly improved the scanning efficiency by increasing the diameter of the scanning spot.